THE ACQUISITION OF SHARED PARENTAL RESPONSIBILITY BY SAME-SEX CIVIL UNION PARTNERS - Anne Louw (Obiter, 2022)
The acquisition of parental responsibility in South Africa is currently still determined by the legitimate status of a child (Van Heerden “How the Parental Power is Acquired and Lost” in Van Heerden, Cockrell and Keightley (eds) Boberg’s Law of Persons and the Family (1999) 317 and authority quoted in fn 17). The birth of a legitimate child will vest equal and independent parental responsibility in both parents of the child (s 1(2) of the Guardianship Act 192 of 1993). Legitimate status and the resultant acquisition of parental responsibility can also be achieved through the legitimation of the child per matrimonium subsequens, adoption and artificialfertilisation with the consent of both spouses (Davel and Jordaan Law of Persons (2005) 108-109). In the case of a same-sex civil union it is obvious that the acquisition of shared parental responsibility by both civil union partners through the birth of a legitimate child or the legitimation of a child born out of wedlock, is out of the question. This comment will investigate the possibility of same-sex civil union partners acquiring shared parental responsibility in respect of a child or children born through adoption and artificial fertilisation. Since the children cannot be described as being legitimate or “born from the marriage” between the same-sex civil unionpartners, they will be referred to as children “planned” by the partners themselves. In this way the civil union partners are seen as the intentional parents of the children, that is, the persons who intend to become the legal parents of the child(ren) at birth. The acquisition of parental responsibility by one civil union partner in respect of children born from a previous (heterosexual) marriage or relationship of the other same-sex civil union partner will also briefly be canvassed.